P686 Novel grape-derived prebiotic selectively enhances abundance and metabolic activity of IBD and IBS faecal butyrate producing bacteria in an in vitro model of intestinal fermentation. (27th May 2021) - Oliver, L; Ramió-Pujol, S; Amoedo, J; Malagón, M; Serrano, M; Bahí, A; Lluansí, A; Busquets, D; Pardo, L; Serra-Pagès, M; Aldeguer, X; Garcia-Gil, J
Abstract: Background: Inflammatory Bowel Disease (IBD) and Irritable Bowel Syndrome (IBS) are two intestinal disorders with unknown aetiology. IBD presents two main forms which are Crohn's disease (CD) and ulcerative colitis (UC). It has been reported recently that bacterial communities present in the colon of patients with either IBD or IBS are structurally different compared to those found in healthy individuals. This dysbiosis mainly consists of a decrease of butyrate producing bacteria and, therefore, the recovery of this metabolic group should be at the baseline of any successful treatment. The main goal of this proof-of-concept study was to test the capacity of a new prebiotic of selected dietary fibre obtained from grape to balance the dysbiosis found in patients with different intestinal disorders. Methods: In this study, fresh faecal samples from 6 healthy subjects, 3 CD, 3 UC, and 3 IBS were collected at the Hospital Universitari Dr. Josep Trueta. Fresh samples were diluted 1:5 with fermentation buffer and incubated with 200 mg of prebiotic at 37 ºC under agitation for 72 h. Results were compared with those obtained with various commercial prebiotics after simulating in vitro digestion: inulin, grape pectin, and grape seed extract (GSPE). Total DNA was extracted and the abundance of butyrate-producing bacterial markers: F. prausnitzii (Fpra), its two phylogroups (PHGI and PHGII), Roseburia spp. (Ros) and S. variabile (Sva) was analysed by qPCR. Bacterial activity was determined by measuring short chain fatty acids (SCFA) concentration (butyrate, acetate, and propionate) by gas chromatography. Results: The abundance of all butyrate-producing bacteria analysed increased after incubation with the new prebiotic. Among them, Ros presented significantly higher abundance values with respect to negative control in healthy, CU, and IBS patients. It also showed a significant increase in all individuals analysed compared to inulin, grape pectin, and GSPE. Fermentation of the tested new prebiotic, produced significantly higher concentrations of SCFA (p < 0.001) when compared to negative control and all other commercial fibres. Acetate concentration was a 241% higher than negative control, followed by butyrate (187%), and propionate (169%). Conclusion: The studied prebiotic produces in vitro an increase of the abundance and enhancement of the metabolism of butyrate-producing bacteria, when compared to commercial prebiotics. These results suggest that this new fibre is a promising prebiotic to be used in promotion of intestinal microbiota restoration at mucosa.